2022
DOI: 10.3390/jof8060604
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Domestic Cats: Environmental Detection of Sporothrix brasiliensis DNA in a Hyperendemic Area of Sporotrichosis in Rio de Janeiro State, Brazil

Abstract: In Brazil, sporotrichosis has transitioned from a rural to urban disease, driven by a shift in the initiation of infection from the accidental inoculation of organic matter to the traumatic implantation of the fungus by cats. Since the emergence of zoonotic sporotrichosis caused by Sporothrix brasiliensis, investigations have largely ignored the environmental habitat of the pathogen due to its association with domestic cats. Therefore, we investigated 18 environmental samples collected from rural areas of two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 51 publications
0
16
0
Order By: Relevance
“…Higher temperatures, heavy rainfall, and flooding are associated with an increase in emerging zoonotic diseases [ 166 , 167 ]. Medically relevant Sporothrix can be detected in the soil of endemic areas where it remains for years [ 168 , 169 ], and it is interesting to hypothesize that water from floods and inundations, a phenomenon increasingly common in Brazil, may also promote the diffusion of Sporothrix propagules in the soil.…”
Section: Trends In the Epidemiology Of Sporothrix ...mentioning
confidence: 99%
“…Higher temperatures, heavy rainfall, and flooding are associated with an increase in emerging zoonotic diseases [ 166 , 167 ]. Medically relevant Sporothrix can be detected in the soil of endemic areas where it remains for years [ 168 , 169 ], and it is interesting to hypothesize that water from floods and inundations, a phenomenon increasingly common in Brazil, may also promote the diffusion of Sporothrix propagules in the soil.…”
Section: Trends In the Epidemiology Of Sporothrix ...mentioning
confidence: 99%
“…[ 1 , 6 , 7 , 8 , 9 ]. Therefore, the drivers of the emergence of pathogenicity in a genus whose core is mostly saprophytic is an intriguing phenomenon which is still poorly understood [ 10 , 11 , 12 , 13 , 14 , 15 , 16 ].…”
Section: A Primer On Sporothrix and Sporotrichosismentioning
confidence: 99%
“…However, few efforts have been carried out to understand the ecological niche of Sporothrix spp. in this geographical area [ 14 ]. Here, Almeida-Silva et al reported the isolation of 18 environmental samples from the hyperepidemic area of Rio de Janeiro, in particular from rural areas with a low cat population density, and were not capable to isolate any fungal colony with morphology similar to Sporothrix spp.…”
mentioning
confidence: 99%
“…Here, Almeida-Silva et al reported the isolation of 18 environmental samples from the hyperepidemic area of Rio de Janeiro, in particular from rural areas with a low cat population density, and were not capable to isolate any fungal colony with morphology similar to Sporothrix spp. [ 14 ]. However, molecular strategies such as nested-PCR and the species-specific PCR for S. brasiliensis were positive for 18 and 5 samples, respectively [ 14 ].…”
mentioning
confidence: 99%
See 1 more Smart Citation